(untitled) (JURNAL KEPERAWATAN, 2015)
ABSTRACT: Breastfeeding (ASI) is the most important baby food, especially in the first months of birth.Exclusive breastfeeding is very influential on the quality of infant health.The fewer the number of babies exclusively breastfed, then the quality of the health of infants and young children will get worse, because the provision of complementary feeding which may cause indigestion which in turn causes growth retardation of children. The aim of research to determine the relationship of the family support system with the attitude of Mother in exclusive breastfeeding in the PHC Ranomuut Perkamil Manado. The research method is analytical observation with cross sectional study, the population of which is breastfeeding infants 0-6 months of age who met the inclusion criteria. The study sample 45 respondents were obtained by using purposive sampling technique.The instruments used are questionnaire support system of family and mother attitude in exclusive breastfeeding. Research results using statistical test Chi Square test at 95% significance level (á 0.05), then the p value = 0,000. This means that the value of p <á (0.05) and the value of OR 53,167. Conclusion have significant correlation between family support system with the attitude Mrs. exclusive breastfeeding in the PHC Ranomuut Perkamil Kota Manado. Advice for a study in order to motivate the nurses in health centers Ranomuut to encourage and disseminate to breastfeeding mothers on the importance of exclusive breastfeeding in infants Keywords : Family Support System, Mother attitude in exclusive breastfeeding ABSTRAK Air Susu Ibu (ASI) adalah makanan bayi yang paling penting terutama pada bulan-bulan pertama kelahiran. Pemberian ASI eksklusif sangat berpengaruh pada kualitas kesehatan bayi. Semakin sedikit jumlah bayi yang mendapat ASI eksklusif, maka kualitas kesehatan bayi dan anak balita akan semakin buruk, karena pemberian makanan pendamping ASI yang tidak tepat dapat menyebabkan gangguan pencernaan yang selanjutnya menyebabkan gangguan pertumbuhan anak Tujuan penelitian untuk mengetahui hubungan support system keluarga dengan sikap Ibu dalam pemberian ASI eksklusif di Puskesmas Ranomuut Perkamil Kota Manado. Metode penelitian yaitu observasional analitik dengan rancangan cross sectional, populasi yaitu ibu menyusui bayi umur 0-6 bulan yang memenuhi kriteria inklusi. Sampel penelitian ini 45 responden yang didapat dengan menggunakan teknik purposive sampling. Instrumen yang digunakan yaitu kuisioner support system keluarga dan sikap Ibu dalam pemberian ASI eksklusif. Hasil penelitian uji statistik menggunakan uji Chi Square pada tingkat kemaknaan 95% (á 0,05), maka didapatkan nilai p = 0,000. Ini berarti bahwa nilai p < á (0,05) dan nilai OR 53,167. Kesimpulan ada hubungan yang bermakna antara support system keluarga dengan sikap Ibu dalam pemberian ASI eksklusif di Puskesmas Ranomuut Perkamil Kota Manado. Saran untuk tempat penelitian dapat memotivasi para perawat di Puskesmas Ranomuut untuk mengajak dan mensosialisasikan kepada Ibu-Ibu menyusui tentang pentingnya ASI eksklusif. Kata kunci : Support System Keluarga, Sikap Ibu dalam pemberian ASI Eksklusif